Community-Based Management Of Chronic Emergencies: Integrating Primary Care And Emergency Response For Asthma And Diabetes Crises (The Review of Diabetic Studies, 2025)
Chronic diseases such as asthma and diabetes frequently lead to acute emergencies when exacerbations are not promptly managed. Traditional emergency services often respond after critical deterioration, highlighting the need for proactive, community-based management systems. This review explores the integration of primary care, emergency response, and community health initiatives in managing chronic emergencies. It examines multidisciplinary approaches, including the roles of community paramedics, telemedicine, and patient self-management education. The study also discusses digital tools, early-warning systems, and collaborative protocols that bridge gaps between hospitals and community settings. Evidence from recent studies (2016–2025) indicates that integrated community-based interventions reduce hospital admissions, improve patient outcomes, and enhance disease control. The review concludes with a strategic framework for strengthening community-level preparedness and response for chronic emergencies under the broader goals of sustainable healthcare delivery and public health resilience.